Analysis of tax policy and income tax evasion in developing countries: the case of Ecuador - Montesdeoca Espín, Lourdes Cumandá (2025)
This research aims to review evasion tax models, policies, and interventions in a comparative scheme, starting with the universal economic theory and then reviewing the neoclassical normative standards and contrasting them with real-world tax practices. For the latter approach, it is essential to consider all the limitations and biases in economic and social contexts present in developing countries such as Ecuador. Even when this final document differs from the original plan, it was divided into two parts and four different strategies to reach the main objective of this investigation. The first scheme used was a systematic economic literature review of traditional and behavioral tax evasion models, evasion estimation methodologies, and a comparison.